Regulatory reform: distinguishing between mutual-benefit and public-benefit entities. Issue 3 (2nd September 2019) - Cordery, Carolyn; Sim, Dalice
Abstract : Purpose: The purpose of this paper is to analyse nonprofit regulation through comparing and contrasting mutual-benefit and public-benefit entities. It ascertains how these entities differ in size, publicness, tax benefits and whether these differences might suggest regulatory costs should be differentiated. Design/methodology/approach: This mixed-methods study utilises financial data, submissions and interviews. Findings: There are stark differences in these two types of regulated nonprofit entities. Members should be the primary monitoring agency/ies for mutual-benefit entities, but financial reports should be understandable to these members. Nevertheless, the availability of tax concessions, combined with the benefits of limited liability, suggest mutual-benefit entities should be regulated and monitored by government in a way sympathetic to their size. Research limitations/implications: As with most research, a limitation is this study's focus on a single jurisdiction. Practical implications: The differences in these entities' characteristics are important for designing regulation. Social implications: Better regulation is likely to require a standard set of financial reporting standards. Government has the right to demand disclosures due to benefits mutual-benefit entities enjoy. Originality/value: In comparison to studies utilising only public-benefit data, this study uses unique data sets to compare public-benefit and mutual-benefit entities and presents nonprofit sector participant's perceptions of these differences in context. This enables analysis of how better regulation could be achieved.